Utilization of Organic Waste into Immunity Protein Products and Its Application in Broiler Chicken Growth - Bahri, Syaiful; Berghuis, Nila Tanyela; Ambarwati, Yuli; Sari, Revita; Nurfaradina, Zaskia Ayu (Stannum : Jurnal Sains dan Terapan Kimia, 2025)
This research is related to utilizing organic liquid waste to be processed into immune protein. The processing stages include a mixture of organic liquid waste in the form of garbage leachate, Zingiberaceae, Crude Palm Oil, beef animal fat, and old coconut water. Mixing was carried out by making two immune protein products that differed in composition and function including protim 1 and protim 2 in knowing the success of the product from the observation of the weight of broilers at harvest. Giving protim 1 in drinking produced broiler weights up to 18 days of the age of 707, 697, and 634 grams. The weight of broilers obtained from the provision of protim 2 in drinking until the end of harvest was 2732, 2670, and 2458 grams. The use of both protims was successfully tested by comparing broilers that did not use protim until harvest, resulting in weights of 1749, 2238, and 2338 grams. FCR and IP values for three broilers consuming both protims resulted in values of 0.66 and 11.34, respectively, with physical characteristics that were slightly hairy compared to broilers that did not consume protim.